Tendências no processamento de frangos de corte: Uso racional da água - Bailone, Ricardo Lacava [UNESP]; Roça, Roberto Oliveira [UNESP] (FapUNIFESP (SciELO), 2017)
Currently, rational use of water has been the subject of discussion of government agencies and non-governmental organizations around the world. Following this trend, increasingly stringent laws should be implemented regarding the use of this natural asset. In a broiler slaughterhouse, water usage occurs widely along the entire flowchart. In this context, the present study aimed to compare consumption of water within a broiler slaughterhouse (large size) with models already proposed and used in other countries in order to identify solutions to mitigate losses from mismanagement. It follows that changes in a few key points of the process would give the industry a more sustainable use of water, like replacement of electronarcose by stunning gas, decreasing of the size of the scalding tank or changing in the process, replacement of pre-cooling by water immersion for pre-cooling by air, decreasing of the water renewal in cooling tanks, changes in the cold generator system in air-conditioned environments, as well as the total or partial reuse of water.
Trends in processing broiler: Rational use of water
Keywords: Consumption; Meat; Poultry; Production; Sustainability